Important Tips for Classroom Management: An Overview - Sokoto, Abdullahi Shehu; Abubakar, Iliyasu (EDUMALSYS Journal of Research in Education Management, 2024)
Classroom is an avenue in learning and teaching; it is a great parcel of school where knowledge is taught. The objective of this paper is to form a review on classroom management (CM) with a view to reveal its importance and concepts. Under this, the concept of classroom management, classroom setting as part of classroom management, teaching aids as per classroom management, some challenges, and conclusion were discussed. It is significant to echo that, classroom management is certainly vital for running a class and achieving goals of education. It is all-inclusive, that all stakeholders should help in achieving classroom management.